Polyvinylamine-Containing Adsorbent by Radiation-Induced Grafting of N-Vinylformamide onto Ultrahigh Molecular Weight Polyethylene Films and Hydrolysis for CO2 Capture - Rojek, T. (American Chemical Society, 2017)
A facile method involving radiation induced grafting of N-vinylformamide (NVF) into the microporous structure of ultrahigh molecular weight polyethylene (UHMWPE) film followed by hydrolysis was used to prepare polyvinylamine (PVAm) containing adsorbent for CO2 capturing. The grafting parameters such as solvent type, monomer concentration, absorbed dose, and reaction time were varied to control the grafting yield (GY, ). The degree of hydrolysis of the grafted poly(N-vinylformamide) and density of the formed amine groups were evaluated. The chemical composition and morphology of PVAm modified films were studied using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM), respectively. The distribution of amine groups across the films was monitored by energy dispersive X-ray spectroscopy (EDX). The static CO2 adsorption characteristic of PVAm modified film (from pure CO2) with a GY of 108 was found to be promising and reached a value of 48.6 mg/g at 25 °C and 1 bar. The breakthrough measurements of PVAm modified film showed an effective CO2 adsorption from binary mixtures with N2 without any significant loss in the performance after six adsorption/desorption cycles. © 2017 American Chemical Society.